Targeting an Essential GTPase Obg for the Development of Broad-Spectrum Antibiotics - Bonventre, Josephine A.; Zielke, Ryszard A.; Korotkov, Konstantin V.; Sikora, Aleksandra E. (PLOS ONE, 2016)
A promising new drug target for the development of novel broad-spectrum antibiotics is the highly conserved small GTPase Obg (YhbZ, CgtA), a protein essential for the survival of all bacteria including Neisseria gonorrhoeae (GC). GC is the agent of gonorrhea, a prevalent sexually transmitted disease resulting in serious consequences on reproductive and neonatal health. A preventive anti-gonorrhea vaccine does not exist, and options for effective antibiotic treatments are increasingly limited. To address the dire need for alternative antimicrobial strategies, we have designed and optimized a 384-well GTPase assay to identify inhibitors of Obg using as a model Obg protein from GC, ObgGC. The assay was validated with a pilot screen of 40,000 compounds and achieved an average Z’ value of 0.58 ± 0.02, which suggests a robust assay amenable to high-throughput screening. We developed secondary assessments for identified lead compounds that utilize the interaction between ObgGC and fluorescent guanine nucleotide analogs, mant-GTP and mant-GDP, and an ObgGC variant with multiple alterations in the G-domains that prevent nucleotide binding. To evaluate the broad-spectrum potential of ObgGC inhibitors, Obg proteins of Klebsiella pneumoniae and methicillin-resistant Staphylococcus aureus were assessed using the colorimetric and fluorescence-based activity assays. These approaches can be useful in identifying broad-spectrum Obg inhibitors and advancing the therapeutic battle against multidrug resistant bacteria.